Peaceful Strategy to Black National Question in Ralph Ellison’s Juneteenth - Khatri, Tilak Bahadur (Pursuits: A Journal of English Studies, 2024)
This article analyzes the theme of Black national liberation as it appears in Ralph Ellison's novel Juneteenth. The study has relevance to probe into the remedies of Black liberation movement in America. The article addresses on the research problems concerning to the black protagonist's inability to identify and deal with an appropriate path that leads the freedom of blacks in American society. The study analyzes the issues through the research approach (methodology) of the Marxist concept of dialectics. According to this theory, the conflict between society's opposing forces is permanent, while any resolution to it is conditional and only temporary. This idea maintains that the key to the liberation of the oppressed nationality and class is the battle against the oppressor nationality and class. One of the novel's two main protagonists, Reverend Hickman, belongs to the oppressed black nationality and class. Hickman seeks to free the downtrodden Blacks from its constraints, but he chooses the incorrect road by making peace with the country's ruling white class. Hickman believes that the battles of Afro-Americans alone cannot end black national oppression; instead, he looks to some heavenly figure from the white race, such as Abraham Lincoln, to grant Afro-Americans their independence, justice, and equality. Bliss was nurtured by Hickman in the hopes that he would become the American equivalent of Abraham Lincoln, but Bliss betrayed Hickman by becoming into the racial baiting white senator Adam Sunraider. Despite Bliss's betrayal, Hickman continues to have faith in Sunraider. The study reveals that this Hickman's message of peaceful approach while dealing with ruling whites keeps the Afro-Americans weak, far from liberating the oppressed black nationality.